Extra-skeletal Ewing sarcoma in a 63-year-old female with a history of triple-negative breast cancer: a case report and literature review - Ho, Man Kit; Safavi, Golnesa; Jeon, Won Jin; Mendoza, Evelyn (Frontiers in Oncology, 2025)
Ewing sarcoma (ES), particularly Extra-skeletal Ewing sarcoma (EES), is a rare, aggressive tumor predominantly affecting adolescents and young adults, yet it can occur in older patients, leading to misdiagnosis and delay in treatment. The standard approach includes surgical resection, chemotherapy, and radiation therapy for unresectable disease. This case report presents a 63-year-old female patient with a history of triple-negative breast cancer, who was discovered to have a soft tissue tumor in the left medial thigh. Initially misdiagnosed as rhabdomyosarcoma, the diagnosis of EES was ultimately confirmed via RNA sequencing revealing the EWSR1-FLI1 fusion gene. She underwent neoadjuvant chemotherapy followed by radical resection of the tumor.